The investigation of the weight loss methods and effects on the elite U23 wrestlers - Cesur, Buğrahan; Sanioğlu, Ahmet (Progress in Nutrition, 2020)
Study Objectives: The weight loss in sports is a method that has been implemented so much in several championships for a long time. It is thought that the athletes will be more successful in a lower weight and are considered to be effective, but it is underestimated that the unconscious weight loss causes health problems and negative effects on organisms. In this study, it was aimed to investigate weight loss methods and effects on elite wrestlers and determining the difference between freestyle and Greco-roman style. Methods: The research consists of a total of 97 wrestlers, who are in the U23 Turkish national team category and lose weight before the competition. For determining the weight loss methods and effects on a wrestler, "The athlete’s weight loss method and effects scale" was used. Mann-Whitney U test was used for comparison of freestyle and Greco-roman style wrestlers’ weight loss methods and effects scale scores. Results: Although there was no significant difference between Greco-roman and freestyle wrestlers in the psychological effect, ergogenic aids, diet, and fluid loss sub-dimensions, physiological effect sub-dimension mean were statistically significant between freestyle and Greco-roman wrestlers (p<0.05). Conclusion: As a result, it was found that wrestlers in both groups (Greco-roman and free-style) had more muscle spasms, respiratory disorders, heart palpitations, and injuries with weight loss. It was also found that both freestyle and Greco-roman wrestlers preferred to reduce fat consumption and run with raincoats, as a weight loss method.